INTERFERENCE OF RUNNING ON BODY COMPOSITION OF INDIVIDUALS SUBMITTED TO RESISTANCE TRAINING. (Fiep Bulletin - online, 2012)
The present study aimed to determine the effect of a 15- minute run on body composition (BC) and muscular hypertrophy in individuals submitted to resistance training (RT). The sample was composed of 60 sedentary adults of both sexes, aged between 18 and 40 years. Subjects were divided into two groups of 30 individuals. Controls (S) performed only RT and the experimental group (SR) undertook RT associated with a 15-minute run. Each intervention was applied for a period of 10 weeks. Before and after this period, waist circumference (WC), waist to hip ratio (WHR), body mass index (BMI), height and body mass were measured. Following training, neither group showed significant differences in BMI, body mass and WHR. However, both groups substantially increased their fat-free mass on median, from 47.43 Kg to 50.15 Kg (p
Keywords: Body Fat; Skinfold Thickness; Muscular hypertrophy.